2021
DOI: 10.1073/pnas.2104194118
|View full text |Cite
|
Sign up to set email alerts
|

The microdynamics of spatial polarization: A model and an application to survey data from Ukraine

Abstract: Although spatial polarization of attitudes is extremely common around the world, we understand little about the mechanisms through which polarization on divisive issues rises and falls over time. We develop a theory that explains how political shocks can have different effects in different regions of a country depending upon local dynamics generated by the preexisting spatial distribution of attitudes and discussion networks. Where opinions were previously divided, attitudinal diversity is likely to persist af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…The model has twelve parameters: three for the groups’ respective internal cohesiveness J, six representing how they relate to each other, K, and three H. They can be estimated qualitatively, as we have done here, informed by publicly available poll data (here, we used [ 7 , 41 , 48 ]).…”
Section: Modelmentioning
confidence: 99%
“…The model has twelve parameters: three for the groups’ respective internal cohesiveness J, six representing how they relate to each other, K, and three H. They can be estimated qualitatively, as we have done here, informed by publicly available poll data (here, we used [ 7 , 41 , 48 ]).…”
Section: Modelmentioning
confidence: 99%
“…Our work focuses on affective polarization and sorting with respect to identity groups among the electorate. However attempts to prevent and reverse polarization must also take account of the mechanisms that enable elite [31,32] and ideological polarization [32,33], and must account for the role of factors such as geography [34] and population and social network structure [35][36][37] in producing mass polarization, in addition to the inter-group and economic factors studied here. We must also remain alert to the circumstances under which polarization can provide benefits [38,39] (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It also determines a variety of explanation mechanisms for spatial polarization, such as factor flow, urban prejudice, agglomeration economy, and knowledge spillover [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Other scholars study the spatial polarization of Japanese land price evolution and Ukrainian public opinion polls with the help of the spatial variation function model, micro-dynamic model, and exploratory spatial analysis [ 42 , 43 ]. Additionally, some scholars measure and explore the level of spatial polarization in the development of urbanization, railway transportation, and scientific and technological innovation, and have found that the regional labor market, economic structure, settlement structure, population density, transportation infrastructure, etc., all affect the development of regional imbalances from different aspects [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%